Strategic Analysis of the Recycler considering Consumer Behavior Based on E-Platform Recycling - Kaiwen Zheng; Hong Cheng; S.A. Edalatpanah; Bin Wang; Zihan Hao; Guang Peng (Discrete Dynamics in Nature and Society, 2022)
Internet + platform recycling is a new model of recycling that provides more ways to recycle WEEE. Considering consumers’ preference for channels, we construct a single-channel reverse supply chain model (Model-S) and two dual-channel reverse supply chain models (Model-DU and Model-DD) consisting of a recycler and an e-platform and consider the unified pricing and differentiated pricing strategies in the dual-channel models. By solving the optimal decisions of members using game theory, we innovatively investigate the influence of channel competition and consumer behavior on e-platform recycling and provide a theoretical basis for recyclers to develop pricing strategies in different situations. We find that it is beneficial for the recycler to build its own channel and adopt the differentiated price strategy (Model-DD); more WEEE also can be recycled in this model. However, the e-platform prefers Model-S or Model-DU, which depends on the consumers’ preference and the disposal revenue of WEEE. In addition, consumers’ preference for e-platform is good for them but harmful for the recycler and has a negative impact on recycling quantities. These results aim to provide a theoretical basis for channel management and pricing strategies in the reverse supply chain and further enrich the managerial insights.